Cover Image, Volume 30, Issue 6. Issue 6 (2nd January 2019) - Blume, Oliver; Back, Michael; Born, Teresa; Smeets, Ralf; Jung, Ole; Barbeck, Mike
Abstract : The cover image is based on the Clinical Article Treatment of a bilaterally severely resorbed posterior mandible due to early tooth loss by Guided Bone Regeneration using customized allogeneic bone blocks: A case report with 24 months follow‐up data by Oliver Blume et al DOI:10.1111/jerd.12388 .